Effect of vitamin D deficiency and replacement on endothelial functions in Behçet's disease - (:unkn) unknown (My University, 2012)
OBJECTIVES: Endothelial dysfunction is previously demonstrated in Behçet's disease (BD) and vitamin D is implicated to affect endothelial functions. We aimed to evaluate the status of serum 25(OH)Vit D3 levels and its association with disease activity, endothelial function and carotis intima media thickness (CIMT) in patients with BD. METHODS: Thirty-six BD (F/M: 22/14, mean age: 39.6 years) patients and 51 healthy controls (F/M: 28/23, mean age: 34.5 years) were studied. Rheumatoid arthritis (RA) (n=33) patients (F/M: 26/7, mean age: 50.82 years) were also enrolled, as a disease control group. Endothelial function was evaluated by brachial artery flow mediated dilatation (FMD) and CIMT with B-Mode ultrasound. The vitamin D-deficient BD patients received 1000 IU Vitamin D3 daily for 3 months. RESULTS: Less than 50 nmol/L levels of 25(OH) Vit D3 were present in 61.1% (n=22) of BD and 35.3% (n=18) of HC (serum 25(OH)Vit D3 levels: BD: 44.5 (9-112) vs HC: 56 (14-125) nmol/lt, p=0.01). CIMT and FMD were also significantly different between BD and HC 0.56 (0.35-9.26) vs. 0.39 (0-0.52) and 5.20 (0.56-30.58) vs. 9.04 (-6.9-34.17), p=0.001 and p=0.02, respectively]. However, no correlation was observed between 25(OH)VitD3 levels and CIMT or FMD (r=0.6, p=0.7 and r=0.03, p=0.8, respectively) at baseline. CIMT measurements improved after replacement therapy (0.56 vs. 0.49, p=0.02), FMD measurements also improved, but not reaching statistical significance (5.2 vs. 8.28, p=0.06). CONCLUSIONS: A high presence of vitamin D deficiency was observed in BD patients from Turkey and replacement of vitamin D had favourable effects on endothelial function.
Keywords: Adult; Female; Humans; Treatment Outcome; Behcet Syndrome; Turkey; Prevalence; Male; Biomarkers; Prospective Studies; Endothelium, Vascular; Brachial Artery; Ultrasonography, Doppler; Vitamin D Deficiency; Vasodilation; Vascular Diseases; Carotid Intima-Media Thickness; Carotid Artery Diseases; Cholecalciferol; Vitamins; Calcifediol